12 Feigned or functional?. (28th May 2019) - Edwards, Mark
Abstract : Mark Edwards is Professor of Neurology at St George's University of London and Consultant Neurologist at the Atkinson Morley Regional Neuroscience Centre at St Georges University Hospital. He has a specialist clinical and research interest in Movement Disorders and in neurophysiological and psychophysical methods for exploring their pathophysiology. He did his PhD at the UCL Institute of Neurology with Professor John Rothwell and Professor Kailash Bhatia and was then a Senior Lecturer and Honorary Consultant Neurologist at UCL and the National Hospital for Neurology and Neurosurgery. Here he built up a specific interest in functional neurological symptoms and developed an NIHR funded research program and specialist clinical diagnostic and treatment service for patients with functional movement disorders. At St George's he is part of an integrated diagnostic and treatment service for functional neurological disorder, and continues also with research and clinical work in movement disorders in general. Abstract: 'Poor Hysterics…first they were treated as victims of sexual trouble…then of moral perversity and mediocrity…then of imagination'. Over a century since William James wrote these words, the status of people with functional neurological disorder remains uncertain and ambiguous. The language of everyday medical discourse betrays this ambiguity: 'Are they real seizures? ... Does he have genuine weakness?...The good news is that there's nothing serious wrong…' In this talk I will explore to what extent clinical and experimental work can help address this issue. While we may not be able to resolve the question of 'feigned or functional?' – perhaps because it is unanswerable in this form – exploring it may make us more aware of our own biases, hidden or not, and the way they affect our interaction and care for people with functional neurological disorder.